2001
DOI: 10.1046/j.0022-202x.2001.01433.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Circadian and Ultradian Rhythms of Skin Surface Properties of Face and Forearm of Healthy Women

Abstract: Biologic rhythms of cells and organisms are well documented and have been extensively studied at the physiologic and molecular levels. For the skin, many circadian changes have been investigated but few systematic studies comparing skin at different body sites have been reported. In this study we investigated facial and forearm skin circadian rhythms in eight healthy Caucasian women. Noninvasive methods were used to assess skin capacitance, sebum excretion, skin temperature, transepidermal water loss, and skin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(71 citation statements)
references
References 29 publications
2
67
2
Order By: Relevance
“…Measurements in female participants were performed in their luteal phase of menstrual cycle (28 ± 2 day cycles). [6]…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Measurements in female participants were performed in their luteal phase of menstrual cycle (28 ± 2 day cycles). [6]…”
Section: Methodsmentioning
confidence: 99%
“…Hot beverages and spicy foods were not allowed during study time. [6] Participants were asked not to perform a strenuous exercise during the study day. Standardized meals were served at fixed hours.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zanello et al (2000) showed that two circadian rhythm clocks (clock and period 1) are expressed in human keratinocytes, melanocytes, and fibroblasts and concluded that circadian mechanisms in skin could influence local responses to radiant energy in cutaneous tissue. LeFur et al (2001) verified circadian rhythms in face and/or forearm skin for multiple properties including sebum excretion, transepidermal water loss, skin temperature and capacitance. They concluded that rhythms of skin surface parameters are detectable and that they vary at different anatomic sites.…”
mentioning
confidence: 96%
“…Also, gently massage into the vellus hair follicles and sebaceous gland on the outside of the Vestibulum nasi [95]- [105].…”
Section: ) Historical Mupirocin Nasal Therapy Administered Tid (Tmentioning
confidence: 99%